Prinsip Kebebasan Belajar Imam Al - Ghazali Dalam Sistem Among Prespektif Ki Hajar Dewantara - Wiwin Fahrudin Yusuf; Moh Badrun Nafi'uddin (SAMAWA, 2021)
Education is a very complex activity. Almost all dimensions of human life are seen in the educational process, either directly or indirectly. Under no circumstances can humans resist the effects of implementing education. Education is also a process in which it finds transformation both within oneself and in the community. Therefore, the correct educational process is to free a person from various confines, intimidation and exploitation. This is a portrait of the world of education which is increasingly concerning, even disturbing many people. This situation implies that the dehumanization of school education becomes something that cannot be separated from life, education seems to be the ghost of society. The dehumanization of education, to borrow Paulo Freire's term, is education that oppresses, curbs, and shackles the subject of learning, both the learner and the teacher himself. The context of the research in this scientific work is to discuss the principle of freedom of learning of Imam Al-Ghazali and how the principle of the system among Ki Hajar Dewanatara's perspective. This research is a library research (Library Research), by discussing the principle of freedom of learning by Imam Al-Ghazali and how the principle of the system among Ki Hajar Dewanatara's perspective. Data collection was carried out with yellow books and books, journals, theses, and other scientific works related to the above discussion. Data analysis is carried out by discussing content (content analysis) which is sometimes found in books and books. Check the validity of the data is done with Credibility (Credibilty). The results of this study indicate that: The basic principle of Imam Al-Ghazali's freedom of learning can be interpreted as a conscious effort that leads to the creation of outer and inner behavior to do good and stay away from evil, to have a complete personality both to himself or to others. And also in the principle of the Among Ki Hajar Dewantara system in the implementation of learning at Ki Hajar Dewantara's school, using the "Among System". In the Among System, every teacher (pamong) as a leader in the educational process is required to behave: Ing Ngarsa Sun Tuladha, Ing Madya Mangun Kasra, Tut Wuri Handhayani.